(3ef GdbGFO Gdi GdbjGOIs - (3Lhfj, fVGds ((3HjQhJs (3OGQ GdTab ddfTQ hGdJhRjYs, 2014)
(3ENJGQJ GdeHQGJ bjGOGJgG GdJQHhjI hGdJYdjejI hGdQYGFjI ef Ohf JYQja Ch eYGjjQ deaghe GdbjGOI hPdc dXQha fTCJgG GdJj LGAJ cESJLGHI SQjYI ddhVY GdPj CaQRJg GdMQH GdCgdjI aj dHfGf Ydi eOi (B15 (3SfI, aJe ENJjGQge HfGA deYGjjQYOjOI bO JJbGWY hJJYGQV eY GdeYGjjQ GdYdejI GdbjGOjI GdeJYGQa YdjgG(B. (3gPG GdaUd (B"(3ef GdbGFO Edi GdbjGOI(B" (3ef cJGH (B"(3QMdI aj GdJWhjQ GdJQHhj(B- (3JLQHI GdeHQGJ(B" (3SjhKb JWhQ eaghe GdbjGOI hGdeeGQSGJ GdbjGOjI NdGd CQHY aJQGJ RefjI(B: (3bHd HQfGeL GdJWhjQ GdEOGQj, CKfGA OQGSI GdJbhje GdPGJj hGdQDjI GdeSJbHdjI HYO GdOQGSI, ceG SjJYQV Edi JWhQ Gdeaghe HebGQfI Hjf GdeDSSGJ GdQYGFjI hGdJYdjejI Ydi GdeSJhi GdRefj hGdeaGgjej(B. (3hJe JCWjQ eaghe GdbjGOI aj GdOQGSI Vef eLehYI eYGjjQ TcdJ GdEWGQ GdeQLYj GdPj EYJeOJg GdeHQGJ ceaghe ddbjGOI GdJQHhjI(B. (3bHd HQfGeL GdJWhjQ GdEOGQj EQJHW eaghe GdbjGOI aj CPgGf GdYGedjf HTNU GdeOjQ ef NdGd GdeeGQSGJ GdJj cGf jbhe HgG, hHYO GdHQfGeL JZjjQ eaghe GdbjGOI ef eOjQ Pj UdGMjGJ hGSYI JJLGhR GdeSGAdI hGdJbjje Edi eOjQ jJacQ aj COGFg, hXgQ eaghe GdbjGOI GdLeGYjI HYO Cf cGfJ aQOjI(B. (3CeG eaghe GdbjGOI QHWG HOQGSI GdJbhje GdPGJj, Hjf eYGjjQ ddOQGSI CKGQJ GdhYj Mhd oHYO LOjO ddbjGOI hgh Cfg jecf JTcjd GdbjGOI hEcJSGHgG ddYGedjf aj ehGbY bjGOjI YOjOI aj GdeDSSI hgj djSJ MUQG HGdeOjQ, aGdbjGOI eLehYI eJQGHWI ef GdeeGQSGJ(B. (3JMbbJ GdeeGQSGJ GdbjGOjI, GdeQJHWI HWHjYI heOi JTcjd GdCWQ GdfXQjI hJchjf KbGaI GdeDSSI HeG jfSLe eY GdQDjI hGdSjGSGJ, dLeYjI GdeHQGJ GdNjQjI aj YOO eMOhO ef GdeDSSGJ, eeG jTjQ Edi Cf GdeeGQSGJ GdbjGOjI GdJj hLOJ aj GdeDSSGJ cGfJ aj HYVgG ZjQ eefgLI heQJHWI Edi MO HYjO HTNU GdeOjQ Ohf Cf JJTcd aj hYj aQjb GdYed(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Leadership; Leadership; (3GdbjGOIs